(untitled) (Minerva. Revista de Filología Clásica, 2019)
Plautus and Titinius alluded in their comedies to the impact that the Lex Oppia had over Roman women, who were forbidden to wear an excessive ornament. This paper deals with the lexical means used by both playwrights to critizice the luxury of women, such as new words or enumerations.